(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
This article presents a comprehensive methodology for developing a digital development strategy for industrial companies. It involves examining current industrial practices, understanding the dynamic interaction of technologies, and defining a strategic plan that will guide the digital transformation vector of industrial companies. The article supports an iterative and flexible strategy development process that includes technology assessment, strategic alignment, risk management, and stakeholder engagement.